Potential Study and Design of Solar Power Plant Using Weighted Overlay Method Based On Spatial Data in Sambas District - Jati, Pandu Lanang Turonggo; Abidin, Zainal; Yandri, Yandri (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
This study aims to analyze and design an effective Solar Power Plant (PLTS) in Sambas Regency using the spatial data-based Weighted Overlay method. Sambas Regency, located in the 3T (Disadvantaged, Frontier, Outermost) area and directly bordering Malaysia, faces the challenges of uneven electricity distribution and the growth of energy demand that continues to increase along with population growth. With significant renewable energy potential in West Kalimantan, especially solar energy reaching 20 GW, this research has high relevance in providing sustainable solutions to support the region's energy needs. A GIS-based Weighted Overlay approach is used to determine the optimal location of PLTS by considering various parameters such as NDVI, NDBI, NDMI, LST, Slope, Rainfall, distance to PLN substation, and existing PLTS location points. The results of this mapping and analysis were then integrated into the technical design of the PLTS using PVSyst software. This research successfully overcomes practical obstacles, such as land protected by the Ministry of Environment and Forestry, by providing detailed solutions that can be implemented. With the continuous growth of energy demand in Sambas Regency, the implementation of utility-scale solar power plants is becoming increasingly urgent. Through economic analysis that includes NPV, PI, IRR, and DPP, this investment can be concluded as feasible. With the application of the right methodology, it is hoped that this research will make a real contribution in supporting Indonesia's efforts to achieve carbon-neutral targets and meet energy needs in border areas that are still unelectrified.